2021
DOI: 10.18805/lr-4648
|View full text |Cite
|
Sign up to set email alerts
|

Gas Chromatography-Mass Spectrometry (GC-MS) based Metabolomics of Promising Chickpea Genotypes against Callosobruchus chinensis (L.)

Abstract: Background: The pulse beetle, Callosobruchus chinensis L. is one of the main biotic threats to chickpea in both field and storage in the world. The evaluation of chickpea genotypes for pulse beetle resistance has increased motivation for the identification and application of host plant resistance as a critical component of pest management. Methods: In the present study, different chickpea genotypes were evaluated under laboratory conditions to identify the antixenosis, antibiosis and GC-MS based untargeted met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Among the seven compounds identified four compounds viz., Hexadecanoic acid, methyl ester; n-Hexadecanoic acid; 9, 12-octadecadienoic acid (Z, Z) and Octadecaenoic acid were observed in all the four lines including susceptible check with some difference in per cent peak area. The compounds viz., Hexadecanoic acid, methyl ester; n-Hexadecanoic acid and 9, 12-octadecadienoic acid (Z,Z) were reported while studying bruchid resistant and susceptible lines in chickpea (Reddy et al, 2021) and in blackgram (Ragul et al, 2022) through GC-MS analysis. Bharathithasan et al (2021) also reported insecticidal property of Octadecaenoic acid against insect pest of Areca nut.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the seven compounds identified four compounds viz., Hexadecanoic acid, methyl ester; n-Hexadecanoic acid; 9, 12-octadecadienoic acid (Z, Z) and Octadecaenoic acid were observed in all the four lines including susceptible check with some difference in per cent peak area. The compounds viz., Hexadecanoic acid, methyl ester; n-Hexadecanoic acid and 9, 12-octadecadienoic acid (Z,Z) were reported while studying bruchid resistant and susceptible lines in chickpea (Reddy et al, 2021) and in blackgram (Ragul et al, 2022) through GC-MS analysis. Bharathithasan et al (2021) also reported insecticidal property of Octadecaenoic acid against insect pest of Areca nut.…”
Section: Resultsmentioning
confidence: 99%
“…2). The compound 9, 12-Octadecadienoic acid, methyl ester was reported against bruchid infestation in chickpea (Reddy et al, 2021). Hexadecanoic acid, 1-(hydroxymethyl)-1, 2-ethanediyl ester and Hexadecanoic acid, 2-oxiranyl methyl ester were known to have insecticidal properties against insect pest of Areca nut (Bharathithasan et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, pathogen infection reduced several compounds such as myo-inositol, acetic acid, D-manitol, D-ribose and D-galactopyranoside. Those accumulated metabolites are pathogenesis-related (PR) metabolites which are produced et al, 2021) and some responsible for resistance against pests (Reddy et al, 2021). Higher intensities of fatty acids such as ethanedioic and stearic acids were observed in all treated plants.…”
Section: Metabolic Profiles and Changes Of Metabolites During Plant-p...mentioning
confidence: 97%